Oxidant/Antioxidant Status Is Impaired in Sepsis and Is Related to Anti-Apoptotic, Inflammatory, and Innate Immunity Alterations - Marianna Miliaraki; Panagiotis Briassoulis; Stavroula Ilia; Kalliopi Michalakakou; Theodoros Karakonstantakis; Aikaterini Polonifi; Kalliopi Bastaki; Efrossini Briassouli; Konstantinos Vardas; Aikaterini Pistiki; Maria Theodorakopoulou; Theonymfi Tavladaki; et al. (Antioxidants, 2022)
Oxidative stress is considered pivotal in the pathophysiology of sepsis. Oxidants modulate heat shock proteins (Hsp), interleukins (IL), and cell death pathways, including apoptosis. This multicenter prospective observational study was designed to ascertain whether an oxidant/antioxidant imbalance is an independent sepsis discriminator and mortality predictor in intensive care unit (ICU) patients with sepsis (n = 145), compared to non-infectious critically ill patients (n = 112) and healthy individuals (n = 89). Serum total oxidative status (TOS) and total antioxidant capacity (TAC) were measured by photometric testing. IL-6, -8, -10, -27, Hsp72/90 (ELISA), and selected antioxidant biomolecules (Ζn, glutathione) were correlated with apoptotic mediators (caspase-3, capsase-9) and the central anti-apoptotic survivin protein (ELISA, real-time PCR). A wide scattering of TOS, TAC, and TOS/TAC in all three groups was demonstrated. Septic patients had an elevated TOS/TAC, compared to non-infectious critically ill patients and healthy individuals (p = 0.001). TOS/TAC was associated with severity scores, procalcitonin, IL-6, -10, -27, IFN-γ, Hsp72, Hsp90, survivin protein, and survivin isoforms -2B, -ΔΕx3, -WT (p < 0.001). In a propensity probability (age-sex-adjusted) logistic regression model, only sepsis was independently associated with TOS/TAC (Exp(B) 25.4, p < 0.001). The AUCTOS/TAC (0.96 (95% CI = 0.93–0.99)) was higher than AUCTAC (z = 20, p < 0.001) or AUCTOS (z = 3.1, p = 0.002) in distinguishing sepsis. TOS/TAC, TOS, survivin isoforms -WT and -2B, Hsp90, IL-6, survivin protein, and repressed TAC were strong predictors of mortality (p < 0.01). Oxidant/antioxidant status is impaired in septic compared to critically ill patients with trauma or surgery and is related to anti-apoptotic, inflammatory, and innate immunity alterations. The unpredicted TOS/TAC imbalance might be related to undefined phenotypes in patients and healthy individuals.